ANALYSIS OF THE FACTORS OF SOCIAL INNOVATION AND COMPETITIVENESS IN HUNGARY - Lipták, Katalin (PEOPLE: International Journal of Social Sciences, 2019)
To interpret social innovation, it is possible to attribute the specialty of employment to the peripheral regions. Yet, the latest development of new products, services and new methodologies, driven by social values, initiated and implemented by social players, which interprets new social interactions as a backward process of social development, places social innovation as the main point of employment. Competitiveness is a particular importance not only in terms of world economic but also regional economic and local economic development. In this paper, it was examined the values of the Regional Competitiveness Index (RCI) in Hungary and the best-known social innovations in these regions. The second aim of the research is to explore and compare the relationship between competitiveness and social innovations at regional level in Hungary. As a result of this research it can be stated that the social innovations presented will contribute to improving the quality of life of people living in rural areas and people with disabilities in urban areas through employment.